Composite electrode material, preparation method thereof and lithium ion battery

By introducing fast ion conductors into micron-scale electrode materials to form ion channels, the problem of stable lithium storage at low temperatures of micron-scale electrode materials is solved, and the excellent lithium storage performance of lithium-ion batteries in extremely low temperature environments is achieved, and the preparation cost is reduced.

CN119725501AActive Publication Date: 2025-03-28CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510084085.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-03-28
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The prior art cannot effectively solve the problem of stable lithium ion storage of micron-scale electrode materials at low temperatures, resulting in a significant decline in the performance of lithium ion batteries in low temperature environments.

Method used

A composite electrode material is adopted, which is a micron-scale dense nanocrystal, with a polycrystalline structure inside, and the internal grains are nano-scale electrode material. Fast ion conductors are distributed at the boundaries of the internal grains to form ion channels to achieve rapid ion transport.

Benefits of technology

It realizes the stable lithium ion storage of micron-scale electrode materials at low temperatures, improves the lithium storage performance of lithium-ion batteries in extremely low temperature environments, and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725501A_ABST
    Figure CN119725501A_ABST
Patent Text Reader

Abstract

The invention discloses a composite electrode material, a preparation method thereof and a lithium ion battery, and belongs to the technical field of electrode materials. The composite electrode material is a micron-sized compact nanocrystal, the micron-sized compact nanocrystal is of a micron-sized mixed mosaic structure, the interior of the micron-sized compact nanocrystal is of a polycrystalline structure, internal crystal grains are nano-sized electrode materials, and fast ion conductors are distributed at boundaries of the internal crystal grains. The method is applied to the aspect of low-temperature lithium ion batteries, the problem that stable lithium ion storage of a micron-sized electrode material at low temperature cannot be achieved in the prior art is solved, and efficient lithium storage of the electrode material in a low-temperature service environment can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to a composite electrode material, a preparation method thereof and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and relatively light weight. However, the performance of standard lithium-ion batteries will drop significantly at low temperatures, mainly due to factors such as increased viscosity of the electrolyte, decreased conductivity, and reduced activity of the electrode materials. In order to improve the low-temperature energy storage performance of lithium-ion batteries and enable them to be used in low-temperature fields such as high altitudes, high latitudes, and space, the current focus is on modifying the electrolyte. Electrode materials are key components that determine the overall energy and power density of batteries. However, there are few reports on research on improving their intrinsic low-temperature energy storage performance, especially for micron-sized electrode materials that are more practical.

[0003] In order to improve the performance of electrode materials in low-temperature service environments, the morphology and crystal structure of electrode material particles are usually designed, such as using nanomaterials or special porous structures to enhance the reactivity and conductivity of electrode materials. Chinese patent CN116632201A discloses a high-performance lithium-ion battery low-temperature negative electrode material-amorphous tin / carbon nanotube composite, which adopts a nano-scale strategy to compound nano-scale amorphous tin and carbon nanotubes to achieve higher low-temperature capacity and good cycle performance, but the volume energy density of the nano-scale finished product is low, so the cost is high; Chinese patent CN116404236A discloses a niobium-based low-temperature lithium-ion battery, which adopts a carbon coating strategy to coat niobium pentoxide with carbon to improve its conductivity, thereby giving full play to the low-temperature performance of niobium pentoxide, but the improvement effect of the carbon coating strategy is limited, resulting in a small improvement in the low-temperature performance of the material.

[0004] Large-sized micron-sized electrode materials are conducive to obtaining high quality and volume energy density, which can meet the needs of future device miniaturization and are more practical. However, the bulk ion transport process of large-sized, high-density micron-sized electrode materials is slow, especially at low temperatures. Therefore, the development of micron-sized electrode materials with strong low-temperature adaptability, so that they can still store lithium ions efficiently and stably in low-temperature environments, is of great practical significance for the development of lithium-ion battery technology. Summary of the invention

[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to overcome the problem that the prior art cannot solve the stable lithium ion storage of micron-sized electrode materials at low temperatures, and propose a composite electrode material that can realize efficient lithium storage of electrode materials in a low-temperature service environment, a preparation method thereof, and a lithium-ion battery.

[0006] In order to solve the technical problem, the technical solution adopted by the present invention is:

[0007] On one hand, the present invention provides a composite electrode material, which is a micron-scale dense nanocrystal. The micron-scale dense nanocrystal is a micron-scale mixed mosaic structure with a polycrystalline structure inside. The internal grains are nanoscale electrode materials, and fast ion conductors are distributed at the internal grain boundaries.

[0008] Preferably, the size of at least one dimension of the micron-scale dense nanocrystals is selected from any value in the range of 1-10 μm, the size of the internal grains is selected from any value in the range of 100-200 nm; and the mass proportion of the fast ion conductor in the composite electrode material is selected from any value in the range of 0.1-30%.

[0009] Preferably, the electrode material is selected from any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium titanate, and graphite; the fast ion conductor includes Li, M, and A, where M is at least one of transition metals, In, Al, Ge, and Sn elements, and A is at least one of F, Cl, Br, I, and O, and the molar ratio of Li, M, and A is Li:M:A=(3.2-0.2):(1.2-0.8):(6.2-0.8).

[0010] Preferably, the specific surface area of ​​the micron-sized dense nanocrystals does not exceed 50 m 2 / g, tap density not less than 0.8g / cm 3 .

[0011] Another aspect of the present invention provides a method for preparing the composite electrode material, comprising a precursor preparation step and a precursor calcination step.

[0012] Preferably, the precursor preparation step comprises: grinding or ball-milling the electrode material and the fast ion conductor to obtain a precursor; the precursor calcining step comprises: calcining the ball-milled precursor at less than 650° C. to obtain a composite electrode material.

[0013] Preferably, the precursor preparation step comprises: dissolving a Li source, an M source, and an A source in a solvent to form a mixed solution, adding the electrode material powder to the mixed solution, mixing thoroughly to obtain a solid-liquid mixture, subjecting the solid-liquid mixture to a hydrothermal reaction or a solvothermal reaction, washing and drying after the reaction to obtain a precursor; the precursor calcination step comprises: calcining the precursor obtained by the hydrothermal reaction or the solvothermal reaction at 350-1000°C to obtain a composite electrode material.

[0014] Preferably, in the precursor preparation step, the Li source is selected from at least one of lithium hydroxide, lithium nitrate, lithium sulfate, lithium carbonate, lithium phosphate, lithium hydrogen phosphate, lithium chlorate, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium formate, lithium citrate, lithium tert-butoxide, and lithium benzoate; the molar ratio of Li and M in the Li source and the M source is Li:M=10:1-0.2:1; the molar ratio of Li and A in the Li source and the A source is Li:A=8:1-0.2:1; the concentration of Li ions in the mixed solution is 0.1-10 mol / L; the solvent is one or a mixture of deionized water, methanol, ethanol, ethylene glycol, isopropanol, and acetonitrile; the hydrothermal temperature range of the hydrothermal reaction is 60-240°C, the hydrothermal heating rate is 1-10°C / min, the hydrothermal time is 12-36h, and the reaction pressure is 0.15-60MPa.

[0015] Preferably, in the precursor calcination step, the calcination heating rate is 1-10°C / min, the calcination time is 5-12h, the calcination atmosphere is air, nitrogen, argon, argon-hydrogen mixed gas or vacuum, the background gas flow rate is 10-50mL / min or the vacuum degree is 10 -7 -10 -5 Pa.

[0016] The present invention also provides a lithium ion battery, wherein the electrode material of the lithium ion battery is the composite electrode material described in any of the above technical solutions.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention provides a composite electrode material, in which an ion channel is constructed in the bulk phase of micron-sized electrode particles, wherein the internal grains are nano-sized electrode materials used as lithium storage phases, and fast ion conductors are distributed at the internal grain boundaries, used as fast and continuous bulk ion transmission channels, thereby achieving stable lithium ion storage of micron-sized electrode materials at low temperatures;

[0019] The present invention provides a method for preparing a composite electrode material, which has the characteristics of simple synthesis operation, short time, low energy consumption, and can realize low-cost batch preparation;

[0020] The present invention also provides a lithium-ion battery with excellent lithium storage performance at low temperatures, especially in low temperature environments (below -20°C), and can be used in extreme low temperature environments such as severe cold and high altitudes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A schematic diagram of the structure of a composite electrode material provided by an embodiment of the present invention;

[0022] Figure 2 This is a rate performance diagram of the lithium titanate-lithium lanthanum titanate composite electrode material and nano-scale lithium titanate at room temperature provided in Example 1 of the present invention;

[0023] Figure 3 The lithium titanate-lithium lanthanum titanate composite electrode material provided in Example 1 of the present invention and the nano-scale lithium titanate are heated at -20°C and 200 mA·g -1 Lower cycle performance graph;

[0024] Figure 4 This is a rate performance diagram of the lithium titanate-lithium indium chloride composite electrode material and nano-scale lithium titanate provided in Example 3 of the present invention at -20°C. DETAILED DESCRIPTION

[0025] The technical scheme in the specific embodiment of the present invention will be described in detail and completely in conjunction with the accompanying drawings. Obviously, the described embodiments are only some specific implementation methods of the overall technical scheme of the present invention, rather than all implementation methods. Based on the overall concept of the present invention, all other embodiments obtained by ordinary technicians in this field fall within the scope of protection of the present invention.

[0026] On the one hand, the present invention provides a composite electrode material, such as Figure 1 As shown, the composite electrode material is a micron-sized dense nanocrystal, the micron-sized dense nanocrystal is a micron-sized mixed mosaic structure, the interior is a polycrystalline structure, the internal grains are nano-sized electrode materials, and the internal grain boundaries are distributed with fast ion conductors. The composite electrode material constructs an ion channel in the bulk phase of micron-sized electrode particles, wherein the internal grains are nano-sized electrode materials used as lithium storage phases, and the fast ion conductors are distributed at the internal grain boundaries, used as fast and continuous bulk ion transmission channels, and realize the stable lithium ion storage of micron-sized electrode materials at low temperatures. Furthermore, the fast ion conductor is an oxide system (lithium lanthanum titanate LLTO, lithium lanthanum zirconium oxide LLZO, etc.), a halide system (LiInZrCl, LiInYCl, LiInYF, etc.); the electrode materials are: oxides, polyanions.

[0027] It should be noted that large-sized micron-sized electrode materials are conducive to obtaining high quality and volume energy density, which can meet the needs of future device miniaturization and are more practical. However, the bulk ion transport process of large-sized, high-density micron-sized electrode materials is slow, especially at low temperatures. In order to achieve efficient lithium storage of electrode materials in low-temperature service environments, the existing technical methods usually nano-size electrode materials. However, nano-electrode material particles have low packing density, high specific surface area, serious surface side reactions, and often require a large amount of conductive agents, binders, and electrolytes, resulting in low overall energy density and poor stability of the battery. In response to this problem, the present invention provides an oxide electrode material with grain boundaries filled with fast ion conductors and a preparation method thereof, wherein a large-sized micron-sized lithium titanate-lithium lanthanum titanate / lithium indium chloride composite electrode material is taken as an example, which not only has a high tap density, but also can simultaneously achieve dual rapid transport of ions and electrons in the bulk phase of the material, especially in extremely low temperature environments (below -20°C). It still has high rate performance and long cycle stability. Specifically, unlike the agglomeration or assembly of nano-electrode particles, micron-scale dense nanocrystals are primary particles with significantly different scale ranges. The composite electrode material has large size (ensuring high volume energy density) and network mixed inlay structural characteristics, and has dual rapid ion-electron transmission channels. It can integrate the advantages of high tap density, low specific surface area, and rapid ion transmission, improve its rate performance at room temperature and low temperature, and achieve excellent lithium storage performance at low temperatures, especially in low temperature environments (below -20°C), and can be used in extreme low temperature environments such as severe cold and high altitudes.

[0028] In a preferred embodiment, the size of at least one dimension of the micron-sized dense nanocrystal is selected from any value in the range of 1-10 μm, the size of the internal grain is selected from any value in the range of 100-200 nm; the mass proportion of the fast ion conductor in the composite electrode material is selected from any value in the range of 0.1-30%. This technical solution specifically defines the size of the micron-sized dense nanocrystal, ensures that the composite electrode material is micron-sized, is conducive to obtaining high quality and volume energy density, can meet the future device miniaturization requirements and is more practical. It can be understood that the size of the micron-sized dense nanocrystal can also be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm and any point value within the range, the size of the internal grain can also be 120 nm, 140 nm, 160 nm, 180 nm and any point value within the range, and the mass proportion of the fast ion conductor in the composite electrode material can also be 5%, 10%, 15%, 20%, 25% and any point value within the range.

[0029] In a preferred embodiment, the electrode material is selected from any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium titanate, and graphite; the fast ion conductor includes Li, M, and A, where M is at least one of transition metals, In, Al, Ge, and Sn elements, and A is at least one of F, Cl, Br, I, and O, and the molar ratio of Li, M, and A is Li:M:A=(3.2-0.2):(1.2-0.8):(6.2-0.8).

[0030] In a preferred embodiment, the specific surface area of ​​the micron-sized dense nanocrystals does not exceed 50 m 2 / g, tap density not less than 0.8g / cm 3 .

[0031] It should be noted that the difficulties in preparing the above-mentioned composite electrode materials are: 1) the fast ion conductor accounts for a very small proportion, but needs to be evenly distributed in the bulk phase of the electrode material; 2) the two are stably bonded together through bonding to form micron-sized dense particles.

[0032] Another aspect of the present invention provides a method for preparing the composite electrode material described in any of the above technical solutions, comprising a precursor preparation step and a precursor calcination step.

[0033] In a preferred embodiment, the precursor preparation step includes: grinding or ball milling the electrode material and the fast ion conductor to obtain a precursor; the precursor calcining step includes: calcining the ball-milled precursor at less than 650°C to obtain a composite electrode material. This method utilizes the high fluidity of the fast ion conductor in the glassy state to quickly fill it into the nano-grain boundary of the electrode material, thereby overcoming the above-mentioned difficulties in the preparation of composite electrode materials. Specifically, it includes: mixing the lithium source and the indium source and grinding them thoroughly, then adding lithium titanate to mix them and grinding them thoroughly, and finally ball milling the mixed powder, wherein the rotation speed is 400-600rpm, and the time is 24-48h; calcining the ball-milled precursor, the atmosphere is Ar or N2, the calcination temperature is 250-600°C, the heating rate is 2-5°C / min, and the time is 8-12h.

[0034] In a preferred embodiment, the precursor preparation step includes: dissolving Li source, M source, and A source in a solvent to form a mixed solution, adding electrode material powder to the mixed solution, mixing thoroughly to obtain a solid-liquid mixture, subjecting the solid-liquid mixture to a hydrothermal reaction or a solvothermal reaction, washing and drying after the reaction to obtain a precursor; the precursor calcination step includes: calcining the precursor obtained by the hydrothermal reaction or the solvothermal reaction at 350-1000°C to obtain a composite electrode material. This method forms a fast ion conductor in situ at the boundary between nanocrystalline grains of the electrode material, and also overcomes the above-mentioned difficulties in the preparation of composite electrode materials.

[0035] In a preferred embodiment, the Li source is selected from at least one of lithium hydroxide, lithium nitrate, lithium sulfate, lithium carbonate, lithium phosphate, lithium hydrogen phosphate, lithium chlorate, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium formate, lithium citrate, lithium tert-butoxide, and lithium benzoate; the molar ratio of Li and M in the Li source and the M source is Li:M=10:1-0.2:1; the molar ratio of Li and A in the Li source and the A source is Li:A=8:1-0.2:1; the concentration of Li ions in the mixed solution is 0.1-10 mol / L; the solvent is one or a mixture of deionized water, methanol, ethanol, ethylene glycol, isopropanol, and acetonitrile; the hydrothermal temperature range of the hydrothermal reaction is 60-240°C, the hydrothermal heating rate is 1-10°C / min, the hydrothermal time is 12-36h, and the reaction pressure is 0.15-60MPa.

[0036] In a preferred embodiment, in the precursor calcination step, the calcination heating rate is 1-10°C / min, the calcination time is 5-12h, the calcination atmosphere is air, nitrogen, argon, argon-hydrogen mixed gas or vacuum, the background gas flow rate is 10-50mL / min or the vacuum degree is 10 -7 -10 -5 Pa.

[0037] The above two preparation methods compound lithium lanthanum titanate and lithium indium chloride in lithium titanate. Due to the high ionic conductivity of lithium lanthanum titanate and lithium indium chloride, the ionic conductivity of the composite material is improved, and the lithium storage performance of the composite material is higher than the capacity of lithium titanate alone and lithium lanthanum titanate / lithium indium chloride alone. Due to the support of lithium lanthanum titanate and lithium indium chloride, the formation of large-sized lithium titanate-lithium lanthanum titanate composite electrode materials is induced, which has high tap density and high energy density. The inter-grain boundary ion transmission channels generated by the crystallization of lithium lanthanum titanate and lithium indium chloride between the grain boundaries of lithium titanate crystals realize rapid ion transmission at low temperatures.

[0038] The present invention also provides a lithium-ion battery, wherein the electrode material of the lithium-ion battery is the composite electrode material described in any of the above technical solutions. The lithium-ion battery has excellent lithium storage performance at low temperatures, especially in low temperature environments (below -20°C), and can be used in extreme low temperature environments such as severe cold and high altitudes.

[0039] In order to more clearly and in detail introduce the composite electrode material, the preparation method thereof and the lithium ion battery provided by the embodiments of the present invention, they will be described below in conjunction with specific embodiments.

[0040] Example 1

[0041] Precursor preparation: Weigh 10 mg LiNO3 and 70 mg LaNO3 and dissolve them in 10 mL ethanol, and stir at room temperature for 30 min; then weigh 0.50 mL tetrabutyl titanate and dissolve it in 35 mL isopropanol, and stir at room temperature for 1 h; then mix and stir the two solutions for 30 min; then add 15 mL distilled water and stir vigorously for 5 min, finally transfer the solution to the lining of a 100 mL hydrothermal reactor and add 322 mg lithium titanate powder.

[0042] Hydrothermal step: The above precursor was heated to 180°C at a heating rate of 5°C / min and hydrothermal treatment was performed for 12 h.

[0043] Washing and drying steps: The hydrothermal sample was filtered with ethanol three times and then placed in a forced air oven and dried at 80°C for 12 hours.

[0044] Calcination step: After the above precursor is fully ground, it is placed in a muffle furnace, heated to 400° C. at a heating rate of 5° C. / min and calcined for 6 hours to finally prepare the lithium titanate-lithium lanthanum titanate composite electrode material of this embodiment.

[0045] Example 2

[0046] Precursor preparation: Weigh 15 mg of lithium hydroxide monohydrate and 50 mg of LaNO3 and dissolve them in 10 mL of ethanol, and stir at room temperature for 30 min; then weigh 0.30 mL of titanate isopropanol and dissolve it in 35 mL of ethylene glycol, and stir at room temperature for 1 h; then mix and stir the two solutions for 30 min; then add 15 mL of distilled water and stir vigorously for 5 min, finally transfer the solution to the lining of a 100 mL hydrothermal reactor and add 459 mg of lithium titanate powder.

[0047] Hydrothermal step: The above precursor was heated to 180°C at a heating rate of 5°C / min and hydrothermal treatment was performed for 12 h.

[0048] Washing and drying steps: The hydrothermal sample was filtered with ethanol three times and then placed in a forced air oven and dried at 80°C for 12 hours.

[0049] Calcination step: After the above precursor is fully ground, it is placed in a muffle furnace, heated to 600° C. at a heating rate of 5° C. / min and calcined for 6 hours to finally prepare the lithium titanate-lithium lanthanum titanate composite electrode material of this embodiment.

[0050] Example 3

[0051] Precursor preparation: Weigh 2.600g lithium titanate, 0.154g lithium chloride, and 0.254g indium chloride and add them to a ball mill jar, and add the corresponding mass of 5mm zirconia balls at a mass ratio of 1:20, and seal it. Then put the ball mill jar into a ball mill and rotate forward at 600rpm for 20min, reverse at 600rpm for 20min, and rest for 10min. Repeat the procedure 20 times for ball milling. The above steps must be carried out in an argon / nitrogen environment throughout the process.

[0052] Calcination step: The above precursor is fully ground and placed in a tube furnace. In an argon / nitrogen atmosphere, the temperature is increased to 500°C at a heating rate of 5°C / min and calcined for 12 hours to finally prepare the lithium titanate-lithium indium chloride composite electrode material of this embodiment.

[0053] Performance Testing

[0054] The materials prepared in the above-mentioned Examples 1, 2 and 3 were subjected to performance tests.

[0055] The test results show that the lithium titanate-lanthanum titanate composite electrode material of Example 1 has excellent low-temperature lithium storage performance: at room temperature, it has a mass specific capacity of 180mAh / g; at -20°C, it has a mass specific capacity of 90mAh / g (200mA / g current density), and the capacity retention rate after 200 cycles is close to 99.5% ( Figure 2 and Figure 3 ).

[0056] The test results show that the specific capacity, rate and cycle stability of the lithium titanate-lithium lanthanum titanate composite electrode material obtained in Example 2 are close to those in Example 1.

[0057] The test results show that the lithium titanate-lithium indium chloride composite electrode material of Example 3 has excellent low-temperature lithium storage performance: at -20°C, it has a mass specific capacity of 180 mAh / g, and its rate performance is better than that of nano lithium titanate ( Figure 4 ).

Claims

1. A composite electrode material, characterized in that: The micron-level dense nanocrystal is a micron-level mixed mosaic structure, the interior is a polycrystalline structure, the internal grains are nano-level electrode materials, and fast ion conductors are distributed at the internal grain boundaries.

2. The composite electrode material according to claim 1, characterized in that The size of at least one dimension of the micron-scale dense nanocrystals is selected from any value in the range of 1-10 μm, the size of the internal grains is selected from any value in the range of 100-200 nm; the mass proportion of the fast ion conductor in the composite electrode material is selected from any value in the range of 0.1-30%.

3. The composite electrode material according to claim 1, characterized in that The electrode material is selected from any one of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium titanate, and graphite; the fast ion conductor includes Li, M, and A, where M is at least one of transition metals, In, Al, Ge, and Sn elements, and A is at least one of F, Cl, Br, I, and O, and the molar ratio of Li, M, and A is Li:M:A=(3.2-0.2):(1.2-0.8):(6.2-0.8).

4. The composite electrode material according to claim 1, characterized in that The specific surface area of ​​the micron-sized dense nanocrystals does not exceed 50m 2 / g, tap density not less than 0.8g / cm 3 .

5. The method for preparing a composite electrode material according to any one of claims 1 to 4, characterized in that: The method comprises a precursor preparation step and a precursor calcination step.

6. The method for preparing a composite electrode material according to claim 5, characterized in that: The precursor preparation step comprises: grinding or ball milling the electrode material and the fast ion conductor to obtain a precursor; The precursor calcining step comprises: calcining the ball-milled precursor at a temperature lower than 650° C. to obtain a composite electrode material.

7. The method for preparing a composite electrode material according to claim 5, characterized in that: The precursor preparation step comprises: dissolving a Li source, an M source, and an A source in a solvent to form a mixed solution, adding an electrode material powder to the mixed solution, mixing the mixture thoroughly to obtain a solid-liquid mixture, subjecting the solid-liquid mixture to a hydrothermal reaction or a solvothermal reaction, and washing and drying the mixture after the reaction to obtain a precursor; The precursor calcining step comprises: calcining the precursor obtained by hydrothermal reaction or solvent thermal reaction at 350-1000° C. to obtain a composite electrode material.

8. The method for preparing a composite electrode material according to claim 7, characterized in that: In the precursor preparation step, the Li source is selected from at least one of lithium hydroxide, lithium nitrate, lithium sulfate, lithium carbonate, lithium phosphate, lithium hydrogen phosphate, lithium chlorate, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium formate, lithium citrate, lithium tert-butoxide, and lithium benzoate; the molar ratio of Li and M in the Li source and the M source is Li:M=10:1-0.2:1; the molar ratio of Li and A in the Li source and the A source is Li:A=8:1-0.2:1; the concentration of Li ions in the mixed solution is 0.1-10 mol / L; the solvent is one or a mixture of deionized water, methanol, ethanol, ethylene glycol, isopropanol, and acetonitrile; the hydrothermal temperature range of the hydrothermal reaction is 60-240°C, the hydrothermal heating rate is 1-10°C / min, the hydrothermal time is 12-36h, and the reaction pressure is 0.15-60MPa.

9. The method for preparing a composite electrode material according to claim 6 or 7, characterized in that: In the precursor calcination step, the calcination heating rate is 1-10°C / min, the calcination time is 5-12h, the calcination atmosphere is air, nitrogen, argon, argon-hydrogen mixed gas or vacuum, the background gas flow rate is 10-50mL / min or the vacuum degree is 10 -7 -10 -5 Pa.

10. A lithium ion battery, characterized in that: The electrode material of the lithium-ion battery is the composite electrode material according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Niobium-based low-temperature lithium ion battery

    CN116404236A

  • Low-temperature lithium ion battery negative electrode material and preparation method thereof

    CN116632201A

  • Composite anode material LiMnPO4-Li3V2(PO4)3 / C for lithium ion battery and preparation method of material

    CN103000888A

  • Preparation method for modification of lithium ion battery positive electrode material

    CN107799746A

  • Composite cladded lithium ion cathode material, and preparation method thereof

    CN108206276A